Amplicon targeted resequencing for SLC2A9 and SLC22A12 identified novel mutations in hypouricemia subjects. Issue 7 (26th May 2019) - Zhou, Zhaowei; Wang, Ke; Zhou, Juan; Wang, Can; Li, Xinde; Cui, Lingling; Han, Lin; Liu, Zhen; Ren, Wei; Wang, Xuefeng; Zhang, Keke; Li, Zhiqiang; et al.
Abstract: Background: To identify potential causative mutations in SLC2A9 and SLC22A12 that lead to hypouricemia or hyperuricemia (HUA). Methods: Targeted resequencing of whole exon regions of SLC2A9 and SLC22A12 was performed in three cohorts of 31 hypouricemia, 288 HUA and 280 normal controls. Results: A total of 84 high‐quality variants were identified in these three cohorts. Eighteen variants were nonsynonymous or in splicing region, and then included in the following association analysis. For common variants, no significant effects on hypouricemia or HUA were identified. For rare variants, six single nucleotide variations (SNVs) p.T21I and p.G13D in SLC2A9, p.W50fs, p.Q382L, p.V547L and p.E458K in SLC22A12, occurred in totally six hypouricemia subjects and were absent in HUA and normal controls. Allelic and genotypic frequency distributions of the six SNVs differed significantly between the hypouricemia and normal controls even after multiple testing correction, and p.G13D in SLC2A9 and p.V547L in SLC22A12 were newly reported. All these mutations had no significant effects on HUA susceptibility, while the gene‐based analyses substantiated the significant results on hypouricemia. Conclusion: Our study first presents a comprehensive mutation spectrum of hypouricemia in a large Chinese cohort. Abstract : Our research first combined the next‐generation sequencing method and statistical analysis to identify hypouricemia causative mutations of SLC22A12 and SLC2A9 in Han Chinese samples. Among them, SLC2A9: p.Gly13Asp and SLC22A12: p.Val547Leu were first reported.